Problematika Sarana Prasarana dalam Pembelajaran SKI di MTS 1 Kota Bengkulu - Juwita Purnama Sari; Iwi Permata Sari; Zorian Eldiansyah; Dea Monika; Windriyani Agustin Utami (Lembaga Pengembangan Kinerja Dosen, 2025)
Infrastructure problems have become a significant concern in educational discourse, primarily focusing on how inadequate facilities impede the achievement of educational objectives. This research examines the challenges related to educational infrastructure in teaching Islamic Cultural History (SKI) at MTS 1 Kota Bengkulu. Using a qualitative descriptive approach, the study identifies key issues including limited technological resources, insufficient maintenance funding, and inadequate government oversight. The findings reveal that these limitations significantly impact teaching effectiveness, student engagement, and learning outcomes. The implementation of the Merdeka Curriculum, which emphasizes technology integration, faces particular challenges due to infrastructure deficiencies such as limited electrical outlets and projection equipment. The research proposes comprehensive solutions including improved financial management, strategic resource allocation, teacher professional development, and enhanced stakeholder collaboration. This study contributes to understanding how infrastructure limitations affect specialized subjects like SKI and offers practical recommendations for educational institutions facing similar challenges.